2004
DOI: 10.2304/pfie.2004.2.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Imagining Alternativas to Global, Corporate, New Economy Academic Capitalism

Abstract: In this article, the authors detail the conditions and patterns of academic capitalism and the new economy in US higher education. Subsequently, a conceptual model is offered for considering the international reach and national and local patterns of academic capitalism. Further, a distinctive Mexican case of entrepreneurialism is offered. The article concludes with a discussion of alternatives for a model of a universidad latinoamericana that is grounded in the historical role of Latin American universities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…Meanwhile, the annual budget for federal universities dropped by 24% between 1995 and 2002, with a 70% drop in investment in infrastructure in the same period. It is not that the State is unable to fund an expansion in the public sector, but that successive governments have made a conscious decision to channel investment into the private sector -a phenomenon that has been seen across Latin America (Rhoades et al 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the annual budget for federal universities dropped by 24% between 1995 and 2002, with a 70% drop in investment in infrastructure in the same period. It is not that the State is unable to fund an expansion in the public sector, but that successive governments have made a conscious decision to channel investment into the private sector -a phenomenon that has been seen across Latin America (Rhoades et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on Latin America (e.g. Levy 1986;Torres and Schugurensky 2002;Rhoades et al 2004) have shown how in recent decades the countries have moved from small, elite public systems to diversified systems in which private institutions play a fundamental role. Some of these institutions cater for wealthy elites, but a growing number target lower-income students who are unable to enter the selective public universities.…”
Section: Introductionmentioning
confidence: 99%
“…Reforms should not mimic market-oriented business, as counselled by advocates of the now compromised 'Washington Consensus'. Instead, stakeholders must look to the social relations within the organization and consider those changes that would make it possible to forge substantively value rational links between the allocation of financial resources and the aims agreed by stakeholders (Lauter 2002;Rhoades et al 2004;Scott 2002).…”
Section: Discussionmentioning
confidence: 99%
“…business) cost accounting systems and proper capital (accrual) accounting (see Ciancanelli 2008a). 17 The obvious danger with such proposals is they may provoke efforts to change nonprofit financial management to fit the accounting that is imported rather than innovate a kind of accounting that is compatible with non-pecuniary value rationalities that ought to govern resource allocation in nonprofit organizations (Peters 2004;Rhoades et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…(Rammell, 2006). They offer few explicit examples of the differences in perspectives suggested by the first part of the title: 'Competing Higher Education Futures' and represented by the work of Futurists (Miller, 2007;Milojevic, 2005;Rhoades et al, 2004;Slaughter, 1999;Vincent-Lancrin, 2004). To illustrate, Vincent-Lancrin identifies six Futurist scenarios, each of which could be pursued by at least one university in a country, competing with efforts of other universities promoting other scenarios:…”
Section: Introductionmentioning
confidence: 99%